AN UNUSUAL FINDING: AN OPAL AND CHALCEDONY CORE IN THE GALLEGOS RIVER MIDDLE BASIN (SANTA CRUZ, ARGENTINA - Carballo m., Flavia; Belardi, Juan Bautista; Tiberi, Pedro (Magallania, 2019)
On the Southern sector of a wide canyon called Mack Aike (locally known as Chorrillo Grande) located on the northern margin of the middle Gallegos River, a bulky core (231 mm x 210 mm x 147 mm) with multidirectional scars from knapping an opal and chalcedony block-sized nodule was registered. Within the framework of the regional technology of the Pali Aike Volcanic Field, the finding of this core is unusual. The geological genesis and the macroscopic petrographic characteristics of the block and the technological characteristics of the core are described. The block has a glacial origin and would have been locally available. Despite the attractiveness of the raw materials that make up the core, its fractures and discontinuities turned it of regular and poor knapping quality. This explains tthat 50% of the terminations are broken and forming hinges and that 38.23% of the flakes obtained have been cortical. In addition, the wide distribution and local availability of suitable lithic raw materials contributed to a less intensive exploitation of the core. Its use was opportunistic and it was abandoned.